Protein Intake Among Patients with Insulin-Treated Diabetes is Linked to Poor Glycemic Control: Findings of NHANES Data - Bawadi H; Al-Bayyari N; Tayyem R; Shi Z (Diabetes, Metabolic Syndrome and Obesity, 2022)
Hiba Bawadi,1 Nahla Al-Bayyari,2 Reema Tayyem,1 Zumin Shi1 1Department of Human Nutrition and Food Science, College of Health Sciences, QU-Health, Qatar University, Doha, Qatar; 2Department of Nutrition and Food Processing, Faculty of Al-Huson University College, Al-Balqa Applied University, Al-Salt, JordanCorrespondence: Hiba Bawadi, Tel +974 4403 6586, Email hbawadi@qu.edu.qaBackground: Nutrition therapy is considered a key component of diabetes management. Recently, high-protein diets have gained in popularity. Understanding the glycemic effect of dietary protein among patients with diabetes has been of particular interest.Methods: This study is based on NHANES data of 990 participants aged 40 years and older from the NHANES cohorts of 2011– 2012 and 2013– 2014 surveys. Glycosylated hemoglobin (HbA1c level) was used as indicator of glycemic control. Patients were categorized into quartiles for daily protein intake. Average protein intakes for patients in quartile 1 to quartile 4 were 35.5 g, 58.7 g, 79.9 g, and 131.6 g, respectively. Covariates included in the analysis were gender, age, race, caloric intake, muscle strength, education, income, smoking, sedentary lifestyle, alcohol consumption, and BMI.Results: After controlling for covariates, patients in quartile 4 of protein intake had 261% increased risk of poor glycemic control compared with those in quartile 1 (95% CI: 1.29– 5.30). The association was not attenuated after further control for insulin use (OR = 1.94; 95% CI: 0.89– 4.24). In conclusion, higher protein intake seems related to a worse glycemic control in diabetic subjects.Keywords: protein intake, diabetes, insulin